Corporate Dissolution and Shareholders' Reasonable Expectations - Robert B. Thompson (Washington University Law Quarterly, 1988)
Within the last decade the highest appellate courts in a half dozen states have adopted the reasonable expectations standard as the basis for determining whether involuntary dissolution, a court-ordered buyout of a shareholder, or some other relief is appropriate in a corporation wracked with dissension. Lower appellate courts in other states have also adopted this approach, and two states include a reasonable expectation standard in their statutes. This article analyzes the historical development of the reasonable expectations standard and the implications for its continued use in resolving conflicts within corporations.
Keywords: Close corporations; Stockholders